From Immigrant Entrepreneurship to Plurinational Firms: Evidence from Italy - Alessandro Arrighetti; Daniela Gnarini; Andrea Lasagni; Renata Semenza (Department of Economics and Management, University of Parma, 2021)
The article contributes to the current debate on the relationship between migration and entrepreneurship, highlighting the evolution of processes and practices, from the traditional monoethnic firm towards new models, we defined as "plurinational". It refers precisely to the cases, widespread in the evolving cosmopolitan society, where both entrepreneurs and workers belong to different nationalities. The article outlines the findings of a qualitative research study, based on interviews with a series of entrepreneurs of plurinational firms in Italy. Firstly, we found that plurinational firms originate from "weak ties" (through acquaintances and previous work experiences) rather than "strong ties" (through family and co-ethnic community networks). Secondly, far for being univocal models, we found a variety of plurinational entrepreneurships which derives from different scales of priority assigned by ownership or management to plurinationalism as "opportunity" or plurinationalism as "value".
Keywords: 330; immigrant entrepreneurship; plurinationalism; migration; break-out strategies; organizational diversity; Italy